"Empathy machine": how virtual reality affects human rights attitudes. Issue 5 (3rd July 2020) - Bujić, Mila; Salminen, Mikko; Macey, Joseph; Hamari, Juho
Abstract : Purpose: This study aims to investigate how media content consumed through immersive technology may evoke changes in human rights attitudes. It has been proposed that our inability to empathize with others could be overcome by stepping into another's shoes. "Immersive journalism" has been postulated as being able to place us into the shoes of those whose feelings and experiences are distant to us. While virtual reality (VR) and 360-degree news videos have become widely available, it remains unclear how the consumption of content through immersive journalism affects users' attitudes. Design/methodology/approach: Utilizing a between-subject laboratory-controlled experiment ( N  = 87) this study examined participant scores on the Human Rights Questionnaire before and after consuming 360-degree video immersive journalism content via VR ( n  = 31), 2D ( n  = 29), and Article ( n  = 27) formats. Collected data were analysed using statistical inference. Findings: Results indicate that immersive journalism can elicit a positive attitudinal change in users, unlike an Article, with mobile VR having a more prominent effect than a 2D screen. Furthermore, this change is more strongly affected by users' higher Involvement in the content. Originality/value: These findings are relevant for grasping the distinct effects novel and recently popularized technologies and media have on attitudinal change, as well as inform the current debate on the value of VR as "empathy machines".